Critical importance of appropriate fixation conditions for faithful imaging of receptor microclusters - Stanly,TA; Fritzsche,M; Banerji,S; Garcia,E; Bernardino,de la Serna J; Jackson,DG; Eggeling,C (Biology Open, 2016)
Receptor clustering is known to trigger signalling events that contributeto critical changes in cellular functions. Faithful imaging of suchclusters by means of fluorescence microscopy relies on the applicationof adequate cell fixation methods prior to immunolabelling in order toavoid artefactual redistribution by the antibodies themselves. Previouswork has highlighted the inadequacy of fixation with paraformaldehyde(PFA) alone for efficient immobilisation of membrane-associatedmolecules, and the advantages of fixation with PFA in combinationwith glutaraldehyde (GA). Using fluorescence microscopy, we herehighlight how inadequate fixation can lead to the formation ofartefactual clustering of receptors in lymphatic endothelial cells,focussing on the transmembrane hyaluronan receptors LYVE-1 andCD44, and the homotypic adhesion molecule CD31, each of whichdisplays their native diffuse surface distribution pattern only whenvisualised with the right fixation techniques, i.e. PFA/GA incombination. Fluorescence recovery after photobleaching (FRAP)confirms that the artefactual receptor clusters are indeed introduced byresidual mobility. In contrast, we observed full immobilisation ofmembrane proteins in cells that were fixed and then subsequentlypermeabilised, irrespective of whether the fixative was PFA or PFA/GAin combination. Our study underlines the importance of choosingappropriate sample preparation protocols for preserving authenticreceptor organisation in advanced fluorescence microscopy